2015
DOI: 10.1259/bjr.20140542
|View full text |Cite
|
Sign up to set email alerts
|

Mapping tibiofemoral gonarthrosis: an MRI analysis of non-traumatic knee cartilage defects

Abstract: Objective: Arthroscopy is "the gold standard" for the diagnosis of knee cartilage lesions. However, it is invasive and expensive, and displays all the potential complications of an open surgical procedure. Ultra-high-field MRI now offers good opportunities for the indirect assessment of the integrity and structural changes of joint cartilage of the knee. The goal of the present study is to determine the site of early cartilaginous lesions in adults with non-traumatic knee pain. Methods: 3-T MRI examinations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Comparable regions were established on the human tibial plateau, for example by dividing it into meniscus covered and not-covered regions 33 , or in concentric zones (border and centre rings) 34 . Other studies divided the plateau into three 34 or nine regions 35 , 36 , 4 quadrants 31 , 11 areas in the largest possible elliptical region of interest (ROI) 37 or into 16 quadrants each (4 rows, 4 columns) 38 . Wirth and Eckstein provided a valuable MRI-based algorithm for the clinically increasingly important regional analysis of femorotibial cartilage thickness based on a central cylinder and 4 additional regions in radial arrangement 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Comparable regions were established on the human tibial plateau, for example by dividing it into meniscus covered and not-covered regions 33 , or in concentric zones (border and centre rings) 34 . Other studies divided the plateau into three 34 or nine regions 35 , 36 , 4 quadrants 31 , 11 areas in the largest possible elliptical region of interest (ROI) 37 or into 16 quadrants each (4 rows, 4 columns) 38 . Wirth and Eckstein provided a valuable MRI-based algorithm for the clinically increasingly important regional analysis of femorotibial cartilage thickness based on a central cylinder and 4 additional regions in radial arrangement 30 .…”
Section: Discussionmentioning
confidence: 99%
“…There is general agreement that cartilage damage evaluation with standard MRI examination remains problematic. However, recently cartilage specific MRI sequences were developed with different degrees in specificity and sensitivity [114,115]. Furthermore, there are significant differences in the detection of OA depending on the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…At the medial tibiofemoral joint, the width of the joint space increased and the visualization of the outline of the articular cartilage improved by applying traction. Although the incidence of cartilage lesions has been reported to be almost as common in asymptomatic knees as in the medial and lateral tibiofemoral joints [5], several studies have reported that cartilage lesions occurred preferentially in the medial joint and/or medial femoral condyle in osteoarthritic knees or knees following anterior cruciate ligament reconstruction [22][23][24]. Therefore, MRI examination with traction would be useful in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of MRI are reportedly > 85% for advanced-grade articular cartilage lesions; however, MRI sensitivities are < 30% for early-grade lesions [2][3][4]. Usually, articular cartilage lesions of the knee occur at the articular surface that is not in contact with the meniscus [5]. It is important to depict the outline of the articular cartilage lesion for accurate evaluation.…”
Section: Introductionmentioning
confidence: 99%